Edukasi DAGUSIBU (dapatkan, gunakan, simpan, dan buang) Obat untuk Masyarakat Karang Taruna, Jorong Malana Ponco, Tanah Datar - Rahmi Yosmar; Dita Permatasari; Najmiatul Fitria (Warta Pengabdian Andalas, 2023)
DAGUSIBU stands for get, use, save, and throw away. In this program, people can manage and use drugs properly and correctly. As the frontline in medicine, pharmacists must carry out socialization to create a drug-aware society. The Faculty of Pharmacy Universitas Andalas conducted community service through DAGUSIBU socialization to get an overview of knowledge regarding the management and use of drugs in the Karang Taruna Community in Jorong Malana Ponco, Tanah Datar Regency. Was DAGUSIBU counselling used, followed by filling out the questionnaire about drug use? Of the 34 participants who attended, 16 participants filled out drug use questionnaires. Most participants were women with an age range of 54.81 ± 14.44. From the questionnaire obtained, the initial picture of the Jorong Malano community's knowledge of DAGUSIBU is not very good. Based on these results, it can be concluded that community knowledge about DAGUSIBU can still be increased with continuous socialization and intensive education